Laboratory Tests and Numerical Simulations of Two Anti-Vibration Structures Made by 3D Printing – Comparative Research - Piotr KOWALSKI; Adrian ALIKOWSKI (Archives of Acoustics)
This article presents a comparison of test results from two models of anti-vibration systems (I and II) made employing MJF 3D printing technology and two different materials. The research included laboratory tests and numerical simulations, assuming a linear nature of the mechanical properties for the materials and models of structures. The aim of this research was to assess the consistency between laboratory test and numerical simulation results. In addition, evaluation of the suitability of using MJF technology to produce antivibration systems was conducted. During the laboratory tests, the response of the two models of structures to vibrations generated by an exciter was recorded using a high-speed camera. Subsequent image analysis was performed using the MOVIAS Neo software. The obtained values of vibration displacements and resonant frequencies were used to validate the numerical model created in the Simcenter Femap software. Relative differences between the values of resonant frequencies obtained experimentally and through simulations were determined. In the case of the structural model I, creating its numerical model without considering the nonlinearity of mechanical parameters was found to be unjustified. The comparison of the displacements determined during numerical simulations showed relative differences of less than 16% for both models in relation to the laboratory test results. This comparison result indicates a satisfactory accuracy in simulating this parameter. An assessment of the quality and accuracy of MJF technology-produced prints, led to the conclusion that due to the formation of internal stresses during the print creation, the use of “soft” materials in this technology is problematic.